ESTABLISHING FORMULAS FOR DESIGN OF ROOTS PUMP GEOMETRICAL PARAMETERS WITH GIVEN SPECIFIC FLOW RATE - Thai, Nguyen Hong; Trung, Nguyen Thanh (Vietnam Journal of Science and Technology, 2015)
Roots pumps are quite common in industry as well as in modern life. They can be applied in the lubrication system of the diesel engines, or in the automatic production lines etc. One of the most important specifications of the pump is flow rate, but this parameter itself depends on the speed and the volume of the pump chambers. The speed can be changed through transmission units, and the volume of the pump chambers depends on the profile form of the impellers. Finally, the profile form of the impeller depends on the geometrical parameters. That means in order to calculate the geometrical parameters of the pump, we must establish the relationship between the geometrical parameters of the impeller profile and the specific flow rate. Based on the theoretical results, the authors carried out programming software module to calculate the geometrical parameters to form profiles of the impellers, as well as the specific flow rate. The module is built by embedding AutoLISP language into AutoCad environment, in order to automatically design this type of pumps.